Hubungann Topik Penelitian Self – Efficacy dan Motivasi Belajar dalam Konteks Pendidikan : Analisis Bibliometrik - Zahra, Ghefira Az (Maliki Interdisciplinary Journal, 2025)
Student learning motivation is influenced by various factors, one of which is self-efficacy. High confidence in one's abilities (self-efficacy) is believed to increase students' learning motivation. This research aims to identify trends and frequency of research discussing the relationship between learning motivation and self-efficacy. The results of this research provide insight that self-efficacy has a significant role in supporting and encouraging student learning motivation. Bibliometric analysis conducted shows that learning motivation and self-efficacy are two themes frequently discussed in educational literature. Through a bibliometric approach, this study presents a comprehensive picture of the development of literature and the importance of the relationship between these two concepts. self-efficacy, and students who indicated that the main focus of the research lay in several key words.